Capital Structure and Abnormal Returns : An Empirical Study on the Chinese Market Considering Average Industry Leverage - LU, YANJIE (2014)
This dissertation conducts a study based on an inefficient market, the Chinese market, to detect whether the capital structure has a significant influence on a firm’s performance, and whether the influence is positive or negative. A firm’s cumulative abnormal return is used to represent a firm’s performance. In this dissertation, a panel data including 907 companies across the time period from 2000 to 2013 are collected from Chinese market. Beside firm’s leverage, the price-earnings ratio, the price-to-book value, the firm size, the interest rate, and the beta coefficient are also collected as independent variables in our model. The fixed effect model is applied in processing these data. Due to the characteristic of Chinese market, the firm’s leverage has limited effects on firm’s abnormal returns. The empirical results also indicate that the industry factor plays a part when examining their relationships. The abnormal returns increase with leverage ratio for the overall sample, but decline with firm’s leverage for companies in unregulated industries such as warehousing and transportation industry. Moreover, it is of importance to separate the average gearing ratio of the industry that the firm allocated in from firm’s particular leverage. The firm’s abnormal return rises as the average industry leverage increases. It can be seen that the impact of average industry gearing ratio is more significant than firm’s leverage ratio.